Triassic floras of Argentina: biostratigraphy, floristic events and comparison with other areas of Gondwana and Laurasia - Morel, Eduardo Manuel (2003)
Study of the Triassic floristic record of several stratigraphic units of southern and west‐central Argentina has permitted recognition of five Assemblage Biozones and three Stages, defined on the basis of Assemblage Biozone chronology, analysis of main stratigraphic unconformities, and evolution of basin infill. These stages are each characterised by a floristic events: a) appearance of mesophytic elements and coexistence of Palaeozoic and Mesozoic groups (Barrealian); b) maximum diversification of the Dicroidium Flora (Cortaderitian); and c) decline of the Dicroidium Flora and replacement by morphotypes with strong Jurassic affinity (Florian). The Triassic geological record of Argentina, notable for the remarkable continuity of fossil floras, has great potential for long‐distance correlations. Using floristic events recognised in SW Gondwana, a global chart shows the bio‐ and chronostratigraphic units, and compares them with Triassic floras described from the Eastern Province of extratropical Gondwana, and Laurasia.